2013
DOI: 10.4103/2152-7806.107893
|View full text |Cite
|
Sign up to set email alerts
|

The Evangelismos hospital central nervous system tumor registry: Analysis of 1414 cases (1998-2009)

Abstract: Background:The Evangelismos Hospital central nervous system (CNS) Tumor Registry represents the current effort of the Departments of Neurosurgery and Pathology to collect data for primary and metastatic CNS tumor patients. In the present study, 12-year hospital data (1998-2009) were reviewed and analyzed.Methods:Patients that underwent surgery for CNS tumors for the first time were identified. Histologically confirmed tumor rates by age and gender were compared. Time trends in annual rates for specific tumor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
2
1
1
Order By: Relevance
“…Our previous 12-year (1998–2009) analysis from the highest volume national academic department (Neurosurgery, Evangelismos Hospital, Greece) provided hospitalization times and in-hospital mortality (IHM) rates on adult CNS tumors patients. [ 6 ] Our study indicated relatively high estimates for both parameters that were similar to those from low-volume US centers. [ 6 ]…”
supporting
confidence: 69%
See 3 more Smart Citations
“…Our previous 12-year (1998–2009) analysis from the highest volume national academic department (Neurosurgery, Evangelismos Hospital, Greece) provided hospitalization times and in-hospital mortality (IHM) rates on adult CNS tumors patients. [ 6 ] Our study indicated relatively high estimates for both parameters that were similar to those from low-volume US centers. [ 6 ]…”
supporting
confidence: 69%
“…[ 6 ] Our study indicated relatively high estimates for both parameters that were similar to those from low-volume US centers. [ 6 ]…”
supporting
confidence: 64%
See 2 more Smart Citations